The value of laboratory markers in the differential diagnosis of acute vestibular syndrome - Gokcen, Emre; Demir, Bilgehan; Tuba Savrun, Seyda (Annals of Medical Research, 2021)
Aim: Stroke is one of the leading and most challenging problems in distinguishing between central and peripheral causes of acute vestibular syndrome. This study aims to evaluate the potential utility of neutrophil to lymphocyte ratio (NLR), platelet-lymphocyte ratio (PLR), and gamma-glutamyl transferase (GGT) levels in the differential diagnosis of acute vestibular syndrome. Materials and Methods: This retrospective study included 152 patients diagnosed with vestibular neuritis (VN) and posterior circulation ischemic stroke (PCIS) within the scope of the isolated acute vestibular syndrome (AVS: vertigo, nystagmus, nausea-vomiting, postural instability, and intolerance of head movements). Of all these patients, we listed the ones having normal MRI findings and diagnosed with VN in the department of otorhinolaryngology. The diagnosis of stroke was made through neuroimaging methods (CT and MRI). NLR and GGT levels were compared among the patients diagnosed with VN and PCIS.Results: GGT, NLR, PLR levels were significantly higher in the patients with the PCIS group (p0.05). The AUC (area under the curve) and optimal cutoff values for NLR, PLR, and GGT were analyzed by ROC analysis. According to these results, the diagnostic value of NLR was higher in predicting stroke (AUC: 0.741; 95%CI: 0.652-0.829, p0.001)Conclusion: As a result, NLR, GGT, and PLR can be useful biomarkers for deciding in favor of stroke in the differential diagnosis of VN.
Keywords: Acute vestibular syndrome; vestibular neuritis; posterior circulation ischemic stroke; vertigo; gamma-glutamyl transferase; neutrophil to lymphocyte ratio; platelet-lymphocyte ratio